Investigate the Surface Roughness and Bushing Shape in Friction Drilling Of A7075-T651 and St 37 Steel - Ozek, Cebeli; Demir, Zulkuf (Assoc Information Communication Technology Education & Science, 2013)
Due to the beneficial of the bushing form, the connection length and clamping strength is increased in friction drilling of thin-walled cast materials. In this experimental study 2400, 3600, and 4800 rpm spindle speeds, 50, 75, and 100 mm/min feed rates, 24 degrees, 36 degrees, and 48 degrees tool conical angles were selected. 2, 4, and 6 mm thicknesses of A7075-T651 aluminium alloys and St 37 steel materials were drilled with using 10 mm diameter HSS (High Speed Steel) and WC (Tungsten Carbide) rotating conical tools which have 16 mm cylindrical region length. I was analysed the surface roughness, bushing height and bushing sheet thickness according to the spindle speed, feed rate, tool conical angle, workpiece material thickness, both workpiece and tool material types parameters. Consequently it was discovered that in friction drilling of 2 mm thickness A7075-T651 aluminium alloy, the bushing was formed as petal shape, which limited providing connection length and clamping strength owing to the brittleness of the material. In friction drilling of brittle materials, there were a lot of cracks generated on the bushing shape. The minimum surface roughness values were obtained at 3600 rpm spindle speed and 75 mm/min feed rate conditions friction drilling of St 37 steel material. The surface roughness values of A7075-T651 aluminium alloys were higher than St 37 steel materials. In conditions decreasing the spindle speeds, tool conical angles, and increasing feed rates, the bushing height was increased and bushing wall thickness was decreased.
Keywords: Friction Drilling; Surface Roughness; Bushing Height; Bushing Sheet Thickness